Zeta Potential and Colloidal Stability Predictions for Inorganic Nanoparticle Dispersions: Effects of Experimental Conditions and Electrokinetic Models on the Interpretation of Results - Pochapski, Daniel José; Carvalho Dos Santos, Caio; Leite, Gabriel Wosiak; Pulcinelli, Sandra Helena; Santilli, Celso Valentim (Langmuir, 2021)
In this work, a set of experimental electrophoretic mobility (μe) data was used to show how inappropriate selection of the electrokinetic model used to calculate the zeta potential (ζ-potential) can compromise the interpretation of the results for nanoparticles (NPs). The main consequences of using ζ-potential values as criteria to indicate the colloidal stability of NP dispersions are discussed based on DLVO interaction energy predictions. For this, magnetite (Fe3O4) NPs were synthesized and characterized as a model system for performing electrokinetic experiments. The results showed that the Fe3O4 NPs formed mass fractal aggregates in solution, so the ζ-potential could not be determined under ideal conditions when μe depends on the NP radius. In addition, the Dukhin number (Du) estimated from potentiometric titration results indicated that stagnant layer conduction (SLC) could not be neglected for this system. The electrokinetic models that do not consider SLC grossly underestimated the ζ-potential values for the Fe3O4 NPs. The DLVO interaction energy predictions for the colloidal stability of the Fe3O4 NP dispersions also depended on the electrokinetic model used to calculate the ζ-potential. The results obtained for the Fe3O4 NP dispersions also suggested that, contrary to many reports in the literature, high ζ-potential values do not necessarily reflect high colloidal stability for charge-stabilized NP dispersions.In this work, a set of experimental electrophoretic mobility (μe) data was used to show how inappropriate selection of the electrokinetic model used to calculate the zeta potential (ζ-potential) can compromise the interpretation of the results for nanoparticles (NPs). The main consequences of using ζ-potential values as criteria to indicate the colloidal stability of NP dispersions are discussed based on DLVO interaction energy predictions. For this, magnetite (Fe3O4) NPs were synthesized and characterized as a model system for performing electrokinetic experiments. The results showed that the Fe3O4 NPs formed mass fractal aggregates in solution, so the ζ-potential could not be determined under ideal conditions when μe depends on the NP radius. In addition, the Dukhin number (Du) estimated from potentiometric titration results indicated that stagnant layer conduction (SLC) could not be neglected for this system. The electrokinetic models that do not consider SLC grossly underestimated the ζ-potential values for the Fe3O4 NPs. The DLVO interaction energy predictions for the colloidal stability of the Fe3O4 NP dispersions also depended on the electrokinetic model used to calculate the ζ-potential. The results obtained for the Fe3O4 NP dispersions also suggested that, contrary to many reports in the literature, high ζ-potential values do not necessarily reflect high colloidal stability for charge-stabilized NP dispersions.